Review on Simhanada Guggulu and its Medicinal Properties - Bhardwaj, Upendra; Sharma, Rajkumar (International Research Journal of Ayurveda & Yoga, 2022)
In the current climate, stress and life style changes-related diseases are comparatively more prevalent. Degenerative bone disease is one of them. Simhanada Guggulu is an herbal and mineral combination that is frequently used in therapeutic settings to treat rheumatoid arthritis. It has six constituents and is recommended for both neurological and musculoskeletal conditions. Simhanada Guggulu’s components, Rasa, Guna, Virya, Vipak, and Karma, work to lessen the clinical symptoms of Amavata (Rheumatoid arthritis). The pharmacological characteristics and therapeutic applications of Simhanada Guggulu are discussed in this review paper. utilising a variety of authors, periodicals, and academic works. Here, an effort has been made to discuss how Simhanada Guggulu and the medicines that make it up can be used therapeutically.